PENGARUH METODE PELATIHAN DAN PENGETAHUAN TENTANG LIMBAH ORGANIK TERHADAP KETERAMPILAN PETANI MEMBUAT PUPUK ORGANIK ( Studi Eksperimen Pada Petani di Kabupaten Bogor) - Elfarisna Elfarisna (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
The objective of this research is to find out the effect of training methods and farmers knowledge of organic waste to farmers’ skills in formulating organic fertilizer. The research was conducted in Cihowe village subdistrict Ciseeng Bogor regency with a sample of 80 farmers by using an experiment of 2 x 2 factorial design.The result of the research show that : 1) Discussion method is higher than demonstration method to farmers’ skills in formulating organic fertilizer, 2) There is interaction effect between training methods and farmers’ knowledge of organic waste to their skills in formulating organic fertilizer,3) Farmers with high knowledge on organic waste, who are treated with discussion method is higher than demonstration method to farmer’s skills in formulating organic fertilizer, 4) There is no significant effect of discussion method and demonstration method for those farmers with low knowledge on organic waste to their skills in formulating organic fertilizer.